Mathematical model for determining the level of debt that a company should have in the medium and long term - Leyton Díaz, Victor (2001)
The present investigation work has for fundamental object to link diverse economic, accountant, financial and tributary variables in a mathematical model that allows determine a level of indebtedness that should have a company in the medium one and release term, with the purpose of having the liquidity, solvency and apropiate profitability to fulfill the current and future production programs. This model will allow to calculate the cost of financing of third, increase of capital and self-financing that will allow a good handling of the economics and financialresources of a production company.